(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study was conducted in animal farm and laboratories of the Technical Animal Production Department of Al-Mussaib Technical College during period from 20/9/2018 to 20/4/2019 to investing the effect of pregnancy that resulting from hormonal treatments to estrus synchronization in the blood and metabolic changes in local ewes, the study include twenty ewes with age ranged from 2-4 years, and randomly were distributed in two groups sub groups 10 ewes for each group. for the first group, estrus synchronization were done by injection of the Prostaglandin (PGF2α) hormone using 500 IU with 10 days time difference for. While for the second group intravaginal progesterone sponges containing 10 mg of fluorogestone acetate (FGA) were putted for 12 days period of time , The ewes of the two groups were injected with 500 IU of equine chorionic gonadotropin(eCG) after the sponges were removal. The ewes were naturally mated with high fertility (ram / 10 ewes). The blood samples were Collected for each month and stored at -20C° until assayed. The obtained results indicated that the months of pregnancy had significantly effect (p <0.05) in the average concentration of glucose, total protein, packed cell volume (PCV), and hemoglobin when the hormone Prostaglandin is used as well as months of pregnancy had a significant effect (p <0.01) for total protein, cholesterol, packed cell volume (PCV) and hemoglobin when Vaginal sponges were used.